Comparison between early stage oxygenation behavior of fullerenes and carbon nanotubes - Van Lier, G.; Ewels, C.; Cases-Amat, M.; Suarez-Martinez, Irene; Geerlings, P. (American Scientific Publishers, 2009)
We explore early stage oxygen addition to C 60 buckminsterfullerene, and compare its oxygenation behavior to that of both pristine and defective metallic carbon nanotubes, using ab initio theoretical modeling. For fullerene oxygen addition up to C 60O 4, in general oxygenation preferentially occurs at the pentagon-hexagon bonds ([5,6] type addition), leading to open annulene structures, as opposed to the closed [6, 6] epoxide isomers. For carbon nanotubes the preference for annulene structures is significantly more pronounced as all epoxide addition is endothermic. Higher reaction enthalpies are found for oxidation in the proximity of defects as compared to the pristine sidewalls. In most cases higher reaction enthalpies are found for fullerene oxygenation as compared to carbon nanotubes. Copyright © 2009 American Scientific Publishers.